Discovery and Characterization of a Bilirubin Inducible Green Fluorescent Protein From the Moray Eel Gymnothorax zonipectis - Guarnaccia, Andrew M.; Krivoshik, Sara Rose; Sparks, John S.; Gruber, David F.; Gaffney, Jean P. (Frontiers in Marine Science, 2021)
Since the initial discovery of Aqueoria victoria’s green fluorescence off the coast of Washington’s Puget Sound, biofluorescent marine organisms have been found across the globe. The variety of colors of biofluorescence as well as the variability in the organisms that exhibit this fluorescence is astounding. The mechanisms of biofluorescence in marine organisms are also variable. To fluoresce, some organisms use fluorescent proteins, while others use small molecules. In eels, green biofluorescence was first identified in Anguilla japonica. The green fluorescence in A. japonica was discovered to be caused by a fatty acid binding protein (UnaG) whose fluorescence is induced by the addition of bilirubin. Members of this class of proteins were later discovered in Kaupichthys eels (Chlopsid FP I and Chlopsid FP II). Here, we report the discovery and characterization of the first member of this class of green fluorescent fatty acid binding proteins from the moray eel Gymnothorax zonipectis. This protein, GymFP, is 15.6 kDa with a fluorescence excitation at 496 nm and an emission maximum at 532 nm upon addition of bilirubin. GymFP is 61% homologous to UnaG and 47% homologous to Chlopsid FP I. Here, we report de novo transcriptome assembly, protein expression, and fluorescence spectroscopic characterization of GymFP. These findings extend the fluorescent fatty acid binding proteins into a third family of true eels (Anguilliformes).